Marketing Strategy of Advent hospital bandung OutPatient Departement To Increase Patient Visit - Prabowo, Bhanu; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2015)
Abstract.Background: Advent Hospital Bandung is one of the well known hospital in Bandung. Had been operated since 1950, Advent Hospital Bandung had been through many great improvements in its prime time. However, Advent Hospital Bandung had forgotten to prepare and repair for the future and currently fell under a tight competition today.Method: To understand the condition in Advent Hospital Bandung Outpatient Unit, the researcher using several analysis methods that basically could be classifies as internal and external analysis. The internal analysis concluded by STP analysis, marketing mix, and research while the external was concluded by PEST and 5 forces analysis. The data later combined and used in SWOT analysis.Result and conclusion: From the SWOT analysis it is known that the Advent Hospital Bandung current internal position is weak but the external situation held many opportunities. Therefore the best suitable strategy for Advent Hospital Bandung is stability strategy by proceeding with care which can be done by improve the internal situation so that the hospital can compete for the opportunities. The internal improvement could be done by Advent Hospital Bandung is related with the root cause of the problem which are the elements of marketing mix. Two out of the seven elements had a significant effect while the others had a significant correlation to customer loyalty.Key words: Hospital, marketing strategy, loyalty, satisfaction.